Pendampingan pada Keluarga dengan Balita Gizi Kurang dan Stunting - Susilia Idyawati; Baiq Ricca Afrida; Ni Putu Aryani (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Stunting is a chronic nutritional problem that occurs during the growth and development of toddlers. The indicator of a toddler stating stunting is when the height per age or body length on the graph shows a curve of <-2 SD to <-3SD based on WHO standards. The purpose of this service is to increase the knowledge and attitudes of mothers of toddlers. The implementation method for this activity includes the preparation and evaluation stages. At the preparatory stage, socialization was carried out to mothers who have toddlers and then identified malnourished toddlers by weighing and measuring height, then asking permission for assistance and observing. At the implementation stage, anthropometric measurements will be carried out on 51 toddlers, from 51 toddlers 18 toddlers with malnutrition and stunting will be obtained, then assistance will be provided to families by providing Health Education obtained before mentoring mothers of toddlers who have sufficient knowledge and carried out after mentoring knowledge of mothers of toddlers good, the results of the measurement of nutritional status by weighing the toddler's weight showed an average weight increase of 0.8-1Kg.